2009
DOI: 10.1108/02683940910959762
|View full text |Cite
|
Sign up to set email alerts
|

Negative and positive spillover between work and home

Abstract: Purpose -The purpose of this study is to test a model of the relations between positive and negative work-to-home interference home-to-work interference on perceived stress, and job satisfaction. Design/methodology/approach -The mediating role of negative and positive work-to-home interference (WHI) and home-to-work interference (HWI) was examined. Perceived stress as a mediator was also tested. Data were obtained from a sample of 283 French employees. Findings -The results of structural equation modeling indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(26 citation statements)
references
References 35 publications
2
20
0
4
Order By: Relevance
“…Behan & Drobnic, 2010;Carlson et al, 2010;Calvo-Salguero, Carrasco-Gonzalez, & Salinas Martinez, 2010;Lourel, Ford, Gamassou, Gueguen, & Hartmann 2009;Cohen, 2009;Carly et al, 2002). However there are relatively less studies in the collectivist societies (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Behan & Drobnic, 2010;Carlson et al, 2010;Calvo-Salguero, Carrasco-Gonzalez, & Salinas Martinez, 2010;Lourel, Ford, Gamassou, Gueguen, & Hartmann 2009;Cohen, 2009;Carly et al, 2002). However there are relatively less studies in the collectivist societies (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…First of all, in the CEE context, it is very likely that different factors play key roles in mediating spillover effects than those identified in the predominantly AngloSaxon literature. For example, financial well-being plays a critical role in Hungary, while previous analyses tended to pay less attention to this factor (Jung Jang et al 2012;Lourel et al 2009;Powell and Greenhaus, 2010). In addition to these findings, here are also signs that the accustomed dichotomy of inflexible working conditions for males vs. more flexible working conditions limited to females alone might not be so straightforward in the post-socialist context.…”
Section: G S Wf ⊥mentioning
confidence: 49%
“…Lourel et al (2009) in a research project focused on French employees (n=283) also found that perceived stress partially mediates the relationship between both workhome and home-work interference and job satisfaction. As a result, they argue that organizations that have work-life balance policies benefit from greater employee commitment (Lourel et al 2009).…”
Section: The Positive Effect Of Flexibility In Organizationsmentioning
confidence: 92%
“…Moreover, flexibility might more strongly reduce the negative work-family spillover of specific groups: namely, women, single parents and those who are burdened with heavier (family) workloads (Jang et al 2012). Lourel et al (2009) in a research project focused on French employees (n=283) also found that perceived stress partially mediates the relationship between both workhome and home-work interference and job satisfaction. As a result, they argue that organizations that have work-life balance policies benefit from greater employee commitment (Lourel et al 2009).…”
Section: The Positive Effect Of Flexibility In Organizationsmentioning
confidence: 99%